VD_FINDINFO HC / 2013 / 3 vom 13. Dezember 2012 - VD Tribunal cantonal (2012)
OBLIGATION D'ENTRETIEN, CONJOINT, ENFANT DU CONJOINT, MESURE PROVISIONNELLE | 159 al. 3 CC, 176 al. 1 ch. 1 CC, 278 al. 2 CC, 308 al. 1 let. b CPC (CH)